2005
DOI: 10.3732/ajb.92.11.1887
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interspecific phylogenetic relationships among diploid TriticumAegilops species (Poaceae) based on base‐pair substitutions, indels, and microsatellites in chloroplast noncoding sequences

Abstract: This study analyzes intra- and interspecific variation in chloroplast DNA (cpDNA) in diploid Triticum-Aegilops species. This analysis focused on DNA sequence variation in noncoding regions of cpDNA, which included base-pair substitutions, insertion/deletions (indels, 50 loci pooled), microsatellites (7 loci pooled), and inversions. Nine of 13 Triticum-Aegilops species were successfully identified and genotyped using these data. Sixty-two haplotypes were detected in 115 accessions of 13 diploid species. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 62 publications
6
71
0
Order By: Relevance
“…In total, 89 molecular markers were identified that are able to discriminate unambiguously between A u and A b genomes, at least within set of accessions studied (Table 3). We can speculate that speciation-associated amplification of mobile genetic elements coupled with evolutionary bottlenecks in the history of T. urartu and T. boeoticum could have led to fixation of multiple 'presence' alleles for novel retrotransposon insertions, which is why the proportion of species-specific SSAP markers is relatively high compared to the other marker types Kilian et al 2007;Yamane and Kawahara 2005). Interestingly, despite the recent efforts to investigate diploid wheat diversity, the problem of finding reliable diagnostic markers for A u and A b genomes has not been paid much attention, either due to lack of speciesspecific polymorphic states or because it was not among the aims of a study Goncharov et al 2009;Heun et al 2008;Kilian et al 2007;Sasanuma et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In total, 89 molecular markers were identified that are able to discriminate unambiguously between A u and A b genomes, at least within set of accessions studied (Table 3). We can speculate that speciation-associated amplification of mobile genetic elements coupled with evolutionary bottlenecks in the history of T. urartu and T. boeoticum could have led to fixation of multiple 'presence' alleles for novel retrotransposon insertions, which is why the proportion of species-specific SSAP markers is relatively high compared to the other marker types Kilian et al 2007;Yamane and Kawahara 2005). Interestingly, despite the recent efforts to investigate diploid wheat diversity, the problem of finding reliable diagnostic markers for A u and A b genomes has not been paid much attention, either due to lack of speciesspecific polymorphic states or because it was not among the aims of a study Goncharov et al 2009;Heun et al 2008;Kilian et al 2007;Sasanuma et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Mini-and microsatellites arise from replication slippage and typically occur at higher frequencies and evolve at a faster rate than nonrepetitive indels and base substitutions (Golenberg et al 1993;Kelchner 2000;Yamane et al 2006). While they can be phylogenetically informative (Graham et al 2000;Hamilton et al 2003;Yamane and Kawahara 2005), repetitive regions may also be subject to homoplasy, where repeat regions are lost or gained to produce alleles that are identical in state but have different ancestral histories, so interpretation of such mutations must be done with great care (Doyle et al 1998;Kelchner 2000;Ingvarsson et al 2003). For a more detailed discussion of cpDNA mutations that is specific to Phragmites, please see Freeland (2011), Saltonstall and, and Freeland and Vachon (2012).…”
Section: Introductionmentioning
confidence: 97%
“…speltoides Tausch was the most likely diploid species for the donor of BB and GG genomes. This idea was supported by RFLP analyses of chloroplast DNA (Ogiwara and Tsunewaki 1988;Miyashita et al 1994;Wang et al 1997;Yamane and Kawahara 2005), mitochondrial DNA (Terachi et al 1990) and nuclear polymorphic DNA (Dvorak and Zhang 1990;Mori et al 1995;Sasanuma et al 1996;Huang et al 2002). Previous studies suggested that T. timopheevii ssp.…”
Section: Introductionmentioning
confidence: 85%